MRI Findings of Causalgia of the Lower Extremity Following Transsphenoidal Resection of Pituitary Tumor - D. Ryan Ormond; Augustine L. Moscatello; Raj Murali (Case Reports in Neurological Medicine)
Background. Causalgia is continuing pain, allodynia, or hyperalgesia after nerve injury with edema, changes in skin blood flow, or abnormal sudomotor activity. Here we report a case of lower extremity causalgia following elective transsphenoidal resection of a pituitary tumor in a young man. Clinical Presentation. A 33-year-old man with acromegaly underwent elective sublabial transsphenoidal resection of his pituitary tumor. During the three-hour surgery, the lower limbs were kept in a supine, neutral position with a pillow under the knees. The right thigh was slightly internally rotated with a tape to expose fascia lata, which was harvested to repair the sella. Postoperatively, he developed causalgia in a distal sciatic and common peroneal nerve distribution. Pain was refractory to several interventions. Finally, phenoxybenzamine improved his pain significantly. Conclusions. Malpositioning in the operating room resulted in causalgia in this young man. Phenoxybenzamine improved, and ultimately resolved, his symptoms. Improvement in his pain symptoms correlated with resolution of imaging changes in the distal sciatic and peroneal nerves on the side of injury.